Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA): Environmental and Social Management Plan (ESMP) for Pilot of Climate Smart Agricultural Innovations and Climate Information Service Technologies in Kenya 2023 - Alliance of Bioversity International and CIAT; International Livestock Research Institute (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project activities in Kenya are focused on improving the quality of Climate Smart Agricultural (CSA) practices and information services in the Arid and Semi-Arid Land (ASAL) areas of Kenya. The project seeks to increase awareness and uptake of selected climate-smart agricultural (CSA) practices and improve access to Climate Information Services (CIS), especially by women and the youth. AICCRA-Kenya is also focused on piloting CSA innovations and CIS technologies in farmers’ fields to expand the awareness and application of relevant climate adaption innovations among farmers. In line with this plan, the Alliance of the Bioversity International and CIAT (Alliance) is collaborating with the Africa Conservation Tillage Network (ACTN) and the universities of Murang’a, Chuka, and Taita Taveta to scale out the uptake of validated CSA and CIS and strengthen the resilience of Kenya dryland agriculture and food systems. The delivery model is to set up farmer-led demonstration farms to serve as a platform to introduce innovative farming techniques, showcase best practices, and enhance the skills of local farmers. The planned CSA demonstrations will occur in Murang’a, Embu, Tharaka Nithi, Taita Taveta and Makueni counties between July and December 2023.